2017
DOI: 10.12911/22998993/74287
|View full text |Cite
|
Sign up to set email alerts
|

MICROBIAL FUEL CELL WITH Cu-B CATHODE POWERING WITH WASTEWATER FROM YEAST PRODUCTION

Abstract: With the increasing standard of living, energy consumption increases as well. So, waste production, including wastewater, increases as well. One of the types of wastewater is wastewater from yeast industry. Wastewater from this industry has not only a high pollutants load but it is produced in great amounts as well. Technical devices that can accomplish the wastewater treatment and electricity production from wastewater is a microbial fuel cell. In microbial fuel cells activated sludge bacteria can be used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
3
15
0
1
Order By: Relevance
“…The obtained results are comparable to the results using e.g. carbon or Cu-B alloy as cathode catalyst [25,31]. The fundamental possibility of using of Ni-Co alloy as cathode catalyst of single chamber MFC for municipally wastewater was obtained in this paper.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The obtained results are comparable to the results using e.g. carbon or Cu-B alloy as cathode catalyst [25,31]. The fundamental possibility of using of Ni-Co alloy as cathode catalyst of single chamber MFC for municipally wastewater was obtained in this paper.…”
Section: Discussionsupporting
confidence: 82%
“…But, in real conditions the choice of catalyst is mainly carried out by experimental methods. For this reason experimental research of search a new catalysts for MFCs are still conducted [15,16,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Investigated waste canola oil emulsion (WCOE) was obtained by mixing, in various ratios of water, waste canola oil and the detergent. WCOE was obtained with the use of a mechanical stirrer, with the speed of about 1200 rpm [10][11][12][13][14][15]. Concentration of canola oil and Syntanol DS-10 was equal to 0.0100%, 0.025% and 0.0500%.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are problems with cheap production and storage of this fuel, and that is the reason for the search of new fuels for FCs, including biofuels [3,[6][7][8][9]. Previous studies by the authors [10][11][12][13][14][15] have shown a possibility of electrooxidation (in various electrolytes) of petroleum derivatives and vegetable oils, e.g. canola oil, sun flower oil or grape seed oil.…”
Section: Introductionmentioning
confidence: 99%
“…However, problems with the storage of hydrogen are the reason for the search for new fuels for FCs, eg. crude oil, petroleum derivatives [5][6][7] or biofuels [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%